(untitled) (Research, Society and Development, 2022)
Objective This study aimed to evaluate the action of botulinum toxin type A for mixed gingival smile due to muscle hyperfunction in a female and male sample (n=5) who had 3mm or more of keratinized gingival tissue exposure in a habitual smile. Materials and Methods The protocol used was the application of 8 units of Botulifit® brand Botulinum toxin type A, 2 units in each point, totaling 4 points and 8 units bilaterally. Photographic protocol was established, before and after the procedure, to exemplify the quantitative improvement of gingival exposure and the results of the work. Results The results were evaluated after 30 days (T1) and 5 months (T2) of application, indicating, for the whole sample, a decrease in gingival exposure by the protocol used, even 5 months after the application of botulinum toxin. Conclusion It was concluded from this work that the application of 8 units of botulinum toxin type A is an efficient therapeutic method for the clinical correction of mixed gingival smile due to muscle hyperfunction, presenting little risk of adverse reactions, low pain sensation to puncture and high acceptability of the patient, as its action is temporary and atraumatic.